Evaluation of photo-induced shear strain in monoclinic VTe2 by ultrafast electron diffraction. (1st August 2018) - Nakamura, Asuka; Shimojima, Takahiro; Matsuura, Masatoshi; Chiashi, Yusuke; Kamitani, Manabu; Sakai, Hideaki; Ishiwata, Shintaro; Li, Han; Oshiyama, Atsushi; Ishizaka, Kyoko
Abstract: We investigate photo-induced lattice strains of a monoclinic VTe2 thin flake using ultrafast electron diffraction. After photoexcitation by a 190 fs pulse, we observe diffraction intensity oscillations with periods of 35 and 75 ps, which indicate coherent acoustic phonons of two distinct branches. The oscillations of and diffraction intensities have opposite signs, indicating the change of the diffraction angle due to the shear strain. By numerically simulating these diffraction intensities as a function of the monoclinic angle, we evaluate the amplitude of the photo-induced shear strain.